If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(7X + -1) = 11(3X + 2) Reorder the terms: 5(-1 + 7X) = 11(3X + 2) (-1 * 5 + 7X * 5) = 11(3X + 2) (-5 + 35X) = 11(3X + 2) Reorder the terms: -5 + 35X = 11(2 + 3X) -5 + 35X = (2 * 11 + 3X * 11) -5 + 35X = (22 + 33X) Solving -5 + 35X = 22 + 33X Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '-33X' to each side of the equation. -5 + 35X + -33X = 22 + 33X + -33X Combine like terms: 35X + -33X = 2X -5 + 2X = 22 + 33X + -33X Combine like terms: 33X + -33X = 0 -5 + 2X = 22 + 0 -5 + 2X = 22 Add '5' to each side of the equation. -5 + 5 + 2X = 22 + 5 Combine like terms: -5 + 5 = 0 0 + 2X = 22 + 5 2X = 22 + 5 Combine like terms: 22 + 5 = 27 2X = 27 Divide each side by '2'. X = 13.5 Simplifying X = 13.5
| 100-96=31y-35y | | 6(3X+2)=4(4X+7) | | -14m+8m=6-60 | | 9p+5q=63 | | 0=-9t | | 3(X+0.3)=1-X | | 3t+9t=20-10+26 | | 3x+14x-5=0 | | 7(a+3)=49 | | 3(a-1)=2(a+1) | | 13-13=2w-w | | -97-10x=9x+7 | | 7=7c-7 | | 3x+7=-45+10x | | x-9x=80 | | 4e-9=3 | | 3-0.8X=7-X | | x-w=y | | 2-0.66X=5-X | | -55+7=8n | | 4x+33=11x-30 | | 77-3x=33x+17 | | t+3+8(5+t)= | | X+6=0.5X-2 | | 11-9x=61-44x | | 3-28=5a | | 2x+35=5x+12 | | -114-8x=9x+22 | | 4(2X-7)=0 | | 9+5(t+1)+4t= | | 3x+7=-59-9x | | 10(2X-3)=8X |